Prevalence of vitamin D deficiency in children with cerebral palsy and autism spectrum disorder: a comparative pilot study - Ruzha Pancheva; Albena Toneva; Yana Bocheva; Miglena Georgieva; Krassimira Koleva; Ivan Yankov (Folia Medica)
Aim: This study aims to explore the prevalence of vitamin D deficiency (VDD) among children with cerebral palsy (CP) and autism spectrum disorder (ASD) in Bulgaria, while analyzing associated demographic, nutritional, and biochemical factors. Materials and methods: A cross-sectional study was conducted in Northeastern Bulgaria, involving 95 children (59 with CP and 36 with ASD). Vitamin D status was assessed using biochemical markers and categorized as deficient (<20 ng/mL), insufficient (20-29 ng/mL), or normal (≥30 ng/mL). Statistical comparisons were performed to identify differences across groups. Results: VDD was prevalent in 29.4% of children with CP and 15.8% of those with ASD, with no significant intergroup differences (p=0.492). Demographic analysis revealed significant gender (p<0.001) and ethnic differences (p=0.006). Children with VDD exhibited lower height-for-age Z scores (p=0.002), weight-for-age Z scores (p=0.021), albumin levels (p<0.001), and lymphocyte counts (p=0.011). Normal ferritin levels alongside reduced transferrin and serum iron suggested protein synthesis deficits rather than depleted iron stores. Conclusion: This study, which is the first in Bulgaria to address vitamin D deficiency in children with autism spectrum disorder and cerebral palsy, emphasizes the necessity of tailored interventions and nutritional support. The findings emphasize the role of biological and sociocultural factors in the prevalence of VDD, contributing valuable insights into pediatric health in moderate-climate regions.